Diketopyrrolopyrrole Organic Thin‐Film Transistors: Impact of Alkyl Substituents and Tolerance of Ethylhexyl Stereoisomers. (8th September 2016) - Stolte, Matthias; Suraru, Sabin‐Lucian; Diemer, Patricia; He, Tao; Burschka, Christian; Zschieschang, Ute; Klauk, Hagen; Würthner, Frank
Abstract : Bis(thiophen‐2‐yl)‐diketopyrrolopyrrole (DPP) dyes bearing various alkyl substituents at the amide positions ( n ‐butyl, n ‐pentyl, n ‐hexyl, n ‐heptyl, n ‐octyl, 2‐ethylhexyl) and chlorine (Cl), bromine (Br), or cyano (CN) substituents at the thiophene positions have been synthesized and investigated with regard to their molecular and semiconducting properties. Intense absorption, strong fluorescence, and reversible oxidation and reduction processes are common to all of these dyes. Their characterization as organic semiconductors in vacuum‐processed thin‐film transistors reveals p‐channel operation with field‐effect mobilities ranging from 0.01 to 0.7 cm 2 V −1 s −1 . The highest mobility is found for the DPP dyes bearing the 2‐ethylhexyl substituents, which is surprising, considering that as a result of the chiral substituents, this material is a mixture of ( R, R ), ( S, S ), and ( R, S ) stereoisomers. The high carrier mobility in the films of the DPPs bearing stereoisomerically inhomogeneous ethylhexyl groups is rationalized here by single‐crystal X‐ray diffraction (XRD) analysis in combination with XRD and atomic force microscopy studies on thin films, which reveal the presence of slightly different 2D layer arrangements for the n ‐alkyl and the 2‐ethylhexyl derivatives. For the cyano‐substituted DPPs possessing the lowest LUMO levels, ambipolar transport characteristics are observed. Abstract : Twenty‐four diketopyrrolopyrrole dyes with branched and linear solubilizing alkyl chains and electron‐withdrawing substituents at the aromatic core are investigated as the semiconductor in organic thin‐film transistors. Remarkably, layers of stereoisomeric mixtures of the 2‐ethylhexyl‐substituted derivatives outperform the devices of dyes with n ‐alkyl chains with carrier mobilities as high as 0.7 cm 2 V −1 s −1 .